Prinsip-Prinsip Manajemen Keuangan di Sekolah: Implementasi dan Dampaknya - Khofi, Mohammad Bilutfikal; Wafi, Inngamul (STKIP MAJENANG, 2025)
Increasingly advanced developments have raised society's demands for quality education, forcing schools to manage their finances more effectively, efficiently, and transparently. Applying appropriate financial management principles is very important to ensure that funds are used optimally, to support the quality of education, and to build trust among all stakeholders. This research examines the principles of financial management in schools, focusing on transparency, accountability, effectiveness, and efficiency in managing educational funds. This research uses a literature review method with data collected from various academic sources such as Google Scholar, JSTOR, and ProQuest. The collected data was analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and concluding. Source triangulation was used to test the validity of the data. The results of this research underscore the importance of implementing the principles of transparency, accountability, effectiveness, and efficiency in school finance management. 1) Transparency ensures the disclosure of financial information to all stakeholders. 2) Accountability requires clear responsibility in the management of funds. 3) Effectiveness is determined by the extent to which funds support the achievement of educational goals, and 4) Efficiency emphasizes the optimal use of resources at minimal cost. By applying these financial management principles, schools can build trust, maximize returns on expenditures, and ensure that educational services are of high quality and sustainable. Proper application of these principles is an essential step for the success and sustainability of schools.